Religious Education Values in Gita Savitri Devi's Rentang Kisah and Andori Andriani's Doriyaki Novels - Oktaviana Araminta Putriyanti; Retno Winarni; Muhammad Rohmadi (BIRCU, 2019)
Religious education is one pillar in human life. This article aims to determine the values of religious education contained in literary works, one of which is a novel. Novels are literary works that attract the readers’ attentions the most because of the plot. Many modern novels containing the values of religious education can be imitated. The RentangKisah by Gita Savitri Devi and Doriyaki by AndoriAndriani are modern novels which contain the values of religious education. These can be seen in the life stories of both. Different family life and social environment make these two novels have different religious education values in their stories. This study is a qualitative descriptive study. The data were collected by taking a note the excerpts of Gita and Dori which contain religious education values. This study aims to determine the values of religious education in the RentangKisah and Doriyaki novels. The results of this study are the values of religious education shown by Gita and Dori.